Impact analysis assessment of UAS collision with a human body - Zdeněk Svatý; Pavel Vrtal; Tomáš Mičunek; Tomáš Kohout; Luboš Nouzovský; Michal Frydrýn; Tomáš Blodek; Karel Kocián (PLoS ONE, 2025)
This study investigates the safety risks of Unmanned Aerial System (UAS) collisions with humans, focusing on impact dynamics through controlled crash testing. Utilizing a custom-designed drop mechanism, 49 impact tests were conducted on a Hybrid III anthropomorphic test device at various velocities and kinetic energies (7–24 m/s and 1–280 J). Tested UASs included a range of designs and weights (20 g to over 1 kg). Results demonstrated limitations in using kinetic energy models and peak head acceleration for injury prediction. The Head Injury Criterion showed greater consistency, reflecting the temporal profile of impacts. Findings revealed that UAS structural fragility reduces energy transfer at higher impacts through deformation and fracturing. This work underscores the need for improved testing protocols and nuanced safety standards.